Phenotypic and morphological characterization of in vitro oligodendrogliogenesis - Mokrý, Jaroslav; Karbanová, Jana; Filip, Stanislav; Čížková, Dana; Pazour, Jan; English, D (Stem cells and development, 2008)
The neurosphere assay has been used to maintain neural progenitor cells (NPCs) in the undifferentiated state. These cells are multipotent and gave rise to neurons and glial cells. Here we show that within 10 days of culture, neurospheres contained precursors and differentiated progeny of all three major central nervous system (CNS) cell lineages and these occupied distinct zones. The microenvironment of the inner zone supported cell differentiation. Cells of oligodendroglial lineage generated within the neurosphere were frequently observed. Of these cells, A2B5(+) cells were homogeneously distributed in the neurospheres, NG2(+) cells preferentially occupied the outer zone and O4(+) cells were localized at the inner zone of 10 day-old neurospheres. We prevented a massive cell death of dissociated neurosphere cells seen after differentiation triggered with adhesion and fetal calf serum by adding epidermal growth factor and basic fibroblast growth factor to the culture medium. Under these conditions, less than one third of cells did not express cell specific markers, glial fibrillary acidic protein-positive astroglia represented 43.4%, NG2(+) and/or O4(+) oligodendroglia represented 24.3%, and betaIII-tubulin(+) neurons 3.1% of cells recovered after neurosphere differentiation. We present evidence that oligodendroglial cells differentiate in a stepwise process as a result of their distribution in subsets that represent distinct developmental stages according to antigenic and morphological criteria. These include oligodendrocyte progenitors, preoligodendrocytes, and oligodendrocytes. The highly complex morphology of mature oligodendrocytes was compatible with functional cells.
Keywords: Tubulin; financování organizované; Animals; Mice, Inbred Strains; Proteoglycans; Phenotype; astrocyty; inbrední kmeny myší; proteoglykany; buněčná diferenciace; Antigens; Glial Fibrillary Acidic Protein; antigeny; Mice; kultivované buňky; myši; Astrocytes; Oligodendroglia; Financing, Organized; gliový fibrilární kyselý protein; Cells, Cultured; tubulin; oligodendroglie; Spheroids, Cellular; Cell Differentiation; fenotyp; zvířata; buněčné sféroidy